Bare metal versus drug eluting stents for ST-segment elevation myocardial infarction in the TOTAL trial. (1st December 2017) - Lavi, Shahar; Iqbal, Javaid; Cairns, John A.; Cantor, Warren J.; Cheema, Asim N.; Moreno, Raul; Meeks, Brandi; Welsh, Robert C.; Kedev, Sasko; Chowdhary, Saqib; Stankovic, Goran; Schwalm, J.D.; et al.
Abstract: Background: The safety and efficacy of drug eluting stents (DES) in the setting of ST elevation myocardial infarction (STEMI) is not well established. Methods: In the TOTAL trial, patients presenting with STEMI were randomized to routine thrombectomy versus PCI alone. In this post-hoc analysis, propensity matching was used to assess relative safety and efficacy according to type of stent used. Results: Each propensity-matched cohort included 2313 patients. The composite primary outcome of cardiovascular death, recurrent MI, cardiogenic shock or class IV heart failure within one year was lower in the DES group (HR 0.67; 95% CI 0.54 to 0.84, p = 0.0004). Cardiovascular death (HR 0.61; 95% CI 0.43 to 0.86, p = 0.005), recurrent MI (HR 0.51; 95% CI 0.35 to 0.75, p = 0.0005), target vessel revascularization (HR 0.47; 95% CI 0.36 to 0.62, p < 0.0001) and stent thrombosis (HR 0.60; 95% CI 0.40 to 0.89, p = 0.01) were lower in the DES group. There was no difference in major bleeding between groups. Conclusions: In this observational analysis, the use of DES was associated with improvement in cardiovascular outcomes compared to the use of BMS. These results support the use of DES during primary PCI for STEMI.